2022
DOI: 10.2217/bmm-2021-0531
|View full text |Cite
|
Sign up to set email alerts
|

Examining Variation and Temporal Dynamics of Extracellular Matrix Biomarkers Following Acute Myocardial Infarction

Abstract: Aim: This study investigated an optimal extracellular matrix (ECM) biomarker panel for measurement in acute myocardial infarction (AMI). Materials & methods: Blood samples were collected from 12 healthy volunteers, and from 23 patients during hospital admission (day 1–3) and 6 months following AMI. Protein assays measured: FGFb, MMP-2, -3, -8, -9, osteopontin, periostin, PINP, TGF-β1, TIMP-1, -4 and VEGF. Results: When compared with healthy levels, seven ECM biomarkers were significantly altered in AMI pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Indeed, concentrations of syndecan-4 [27] and osteopontin [28] are reported to peak between Day 1 and 3 after MI, although later peaks are also reported for syndecan-4 [20]. Contrary to the other biomarkers, periostin levels increased during the initial four months, which can be explained by an early suppression post-MI as observed in other studies [29,30], with a later increase related to tissue remodelling. The time-dependent variation in the biomarker concentrations stress the need for standardized sampling time points and multiple measurements.…”
Section: Plos Onementioning
confidence: 56%
“…Indeed, concentrations of syndecan-4 [27] and osteopontin [28] are reported to peak between Day 1 and 3 after MI, although later peaks are also reported for syndecan-4 [20]. Contrary to the other biomarkers, periostin levels increased during the initial four months, which can be explained by an early suppression post-MI as observed in other studies [29,30], with a later increase related to tissue remodelling. The time-dependent variation in the biomarker concentrations stress the need for standardized sampling time points and multiple measurements.…”
Section: Plos Onementioning
confidence: 56%
“…Accumulating evidence indicate that MMP proteins, including MMP3 (also known as stromelysin-1), are closely associated with MI and heart failure [36][37][38][39]. Thus they can be used as biomarkers and potential therapeutic targets for cardiovascular diseases [40][41][42]. Moreover, polymorphisms of the MMP3 gene are correlated with the genetic risk of MI, suggesting a possible contribution of this gene to the occurrence of this condition [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…For example, PINP is a biomarker of collagen type I synthesis that is not specific to myocardial tissue alone. However, we have selected an optimal panel of ECM biomarkers based on previous testing that suggested these biomarkers were altered in AMI patients compared to healthy volunteers [ 19 ]. This study comprises a moderate sample size and is explorative in nature.…”
Section: Discussionmentioning
confidence: 99%
“…The biomarker panel selected for this study comprised the following: MMP-2, MMP-3, MMP-8, MMP-9, periostin, PINP and TIMP-1. In a previous study, we demonstrated that these ECM biomarkers were of interest to investigate in a prognostic setting following AMI [ 19 ]. Specifically, we showed that levels of these biomarkers were significantly altered in AMI patients when compared to healthy volunteers and that these biomarkers were stably expressed in the first 3 days following symptom onset, confirming opportunistic blood sampling during acute hospital admission.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation